Identity and interculturality of the shipibo-conibo community in Cantagallo Lima - Macahuachi Núñez, Luz Carola (2019)
The migration of peoples to the capital has generated a break in the continuity and survival of their customs, their mother tongue. The latter is lost over time. In this case, it was investigated in the population of Shipibos, arriving from the Amazon to Lima, in which evidence was found that attempts to rescue part of that loss. In this article we analyze this intercultural phenomenon, in which, the Shipibo-Conibo in the new urban scene retain their ethnic identity, culture, customs; and its native language. Among the findings, we analyze the role of the Shipiba woman and the jungle school as a pillar for the conservation of that culture.